STRENGTHENING ISLAMIC CHARACTER THROUGH THE MUTABA’AH YAUMIYYAH PROGRAM: A QUALITATIVE STUDY AT SMP AL-IRSYAD SURAKARTA (Pena Cendekia Insani, 2026)
Character education is essential in shaping students’ moral values and behavior. The Mutaba’ah Yaumiyyah book is used to monitor students’ religious and daily activities to support Islamic character development. This study employed a qualitative method through interviews, observations, and document analysis conducted at SMP Al-Irsyad Surakarta. The findings show that the Mutaba’ah Yaumiyyah book helps students develop positive habits such as discipline, responsibility, honesty, and religious commitment through activities including prayers, Quran recitation, charity, and reading Islamic books. It also supports students in using holiday time productively. The implementation of the Mutaba’ah Yaumiyyah book contributes significantly to building students’ Islamic character, although several obstacles remain in maintaining consistency and supervision. The program may inspire other schools to adopt similar character-building strategies.